On the priority use of reactive power compensation devices - Omelchuk , A. (Energy and Automation, 2026)
The analysis of the results of research by scientists on reactive power compensation in the distribution networks of the distribution system operator (DSO) and in the networks of powerful electricity consumers using synchronous motors, which are a common element of electric drives in the technological processes of a number of enterprises, is presented. The author’s comments on the formulation and solution of the tasks of reactive power compensation (RPC) in electrical networks using synchronous motors (SMs) are given. Therefore, it is relevant to determine the limits of the technical and economic characteristics of SMs for their use together with low-voltage capacitor units (LVCU) for RCS in electrical networks of industrial enterprises. The influence of the operating mode of the enterprise and the parameters of the SMs on the economic feasibility of their use for reactive power compensation is studied. The values ​​of the relative economic reactive load of the SMs and the influence of the speed characteristics of the SMs, operating modes of enterprises and the parameters of the electrical network with connected SMs and VCs on its value are obtained. Recieved: 23.01.2026. Recieved: 25.03.2026. Accepted: 17.04.2026.